Extensive genomic analysis in patients with KRAS-mutated solid tumors shows high frequencies of concurrent alterations and potential targets but has limited clinical impact. (2nd December 2022) - Jacobsen, Ida Christine; Spanggaard, Iben; Højgaard, Martin; Belcaid, Laïla; Qvortrup, Camilla; Yde, Christina Westmose; Schmidt, Ane Yde; Nielsen, Finn Cilius; Willemoe, Gro Linno; Dam, Mikkel Seidelin; Lassen, Ulrik; Staal Rohrberg, Kristoffer
Abstract: Background: This study aimed to investigate the distribution and frequency of concurrent alterations in different cancers across KRAS subtypes and in different KRAS subtypes across cancers, and to identify potentially actionable targets and patients who received targeted treatment matched to their genomic profile (GP). Materials and Methods: In this descriptive and single-center study, we included 188 patients with solid tumors harboring KRAS mutations in codon 12, 13, 61, 117, or 146, referred to the Phase 1 Unit, Rigshospitalet, Copenhagen, Denmark from mid-2016 to 2020. Genomic co-alterations were detected with whole-exome sequencing, RNA sequencing, SNP array, and mRNA expression array on fresh biopsies. The study is part of the Copenhagen Prospective Personalized Oncology study (NCT02290522). Results: The majority of patients had colorectal cancer (60.1%), non-small cell lung cancer (11.2%), or pancreatic cancer (10.6%). Most tumors were KRAS -mutated in codon 12 or 13 (93.7%) including G12D (27.1%), G12V (26.6%), G12C (11.7%), and G13D (11.2%). A total of 175 different co-alterations were found, most frequently pathogenic APC and TP53 mutations (55.9% and 46.4%, respectively) and high expression of CEACAM5 (73.4%). Different cancers and KRAS subtypes showed different patterns of co-alterations, and 157 tumors (83.5%) had potentially actionable targets with varying evidence of targetability (assessed using ESMO Scale for Clinical Actionability of molecular Targets). Of the 188 patients included in the study, 15 (7.4%) received treatment matched to their GP (e.g., immunotherapy and synthetic lethality drugs), of whom one had objective partial response according to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1. Conclusion: Performing extensive genomic analysis in patients with known KRAS -mutated solid tumors may contribute with information to the genomic landscape of cancers and identify targets for immunotherapy or synthetic lethality drugs, but currently appears to have overall limited clinical impact, as few patients received targeted therapy matched to their GP.